Peningkatan Fungsi Dan Kualitas Kawasan Hutan Gunung Puntang Melalui Land Management Dengan Pendekatan Konsep Konserv - Rita Sulastini; Erry Mustariani; Okke Rosmaladewi (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Forest areas existence is one of the material bases for regional development. Beside the ablelityÂ to improve the quality of ecosystem through the content of wetland soil, water and the biological environment, forest areas also functions as a life support for the local community for their economy life depend on. But, the trully facts show that many changes and deviations in land use due to various reasons and perceptions, which is causing problems in the sustainability of the area. Therefore, land management is needed used a conservation concept approach. The goal is that land management can be carried out integrated. The locus study is Gunung Puntang Forest Area, Campakamulya Village, Cimaung, Banjaran District, Bandung Regency West Java.Â This research used naturalstic qualitative method, which the researcher directly involved start from submission process, visits, observations and participated in all activities in natural setting. Land management with a conservation approach is carried out based on conservation theory and policy by considering aspects. Includes: 1) historical aspects to maintain the originality area, 2) cultivation aspects to preventive land quality, 3) spatial aspects as a strategic functions areas in accordance with Rencana tata Ruang Wilayah Nasional, and 4) aspects of regional development related to active productivity of community economic development based on forest wetland agriculture. Therefore consistency and applicative coordination are urgently needed between the implementation of area conservation regulations in various programs, as well as need for more detailed cooperation and coordination from various stakeholders to develop areas in an efficient manner, especially for a local communities.